Conserving cultural landscapes
1 online resource (xviii, 393 pages)
Keywords: "New approaches to both cultural landscapes and historic urban landscapes increasingly recognize the need to guide future change, rather than simply protecting the fabric of the past. Challenging traditional notions of historic preservation, Conserving Cultural Landscapes takes a dynamic multifaceted approach to conservation. It builds on the premise that a successful approach to urban and cultural landscape conservation recognizes cultural as well as natural values, sustains traditional connections to place, and engages people in stewardship where they live and work. It brings together academics within the humanities and humanistic social sciences, conservation and preservation professionals, practitioners, and stakeholders to rethink the meaning and practice of cultural heritage conservation, encourage international cooperation, and stimulate collaborative research and scholarship. "--